Amniotic Fluid, Water for the Fruit - Timmerman, Alize (Homœopathic Links, 2012)
Trituration of substances deriving from the human body started in the late nineties of the last century. One important substance, fitting in the row of Placenta, Umbilical cord, DNA, Lac humanum, etc. is Amniotic fluid. Initiated by the Hahnemann Institute of the Netherlands, triturations of Amniotic fluid were carried out in different countries. The results of these triturations are presented in this article on the 1 C to 4 C levels. Next to the materia medica information, insight into the working of the remedy is given by presenting a case of Amniotic fluid and two examples of the way this remedy influences people, both the homeopath and the patient.
Keywords: Amniotic fluid; Sarcodes; Trituration; Baryta carbonica; Mood swings